Enhancing Mergers and Acquisitions (M&A) performance: Analyzing the role of human resource practices in Sri Lanka's telecommunication industry through Lewin's change management model. - S H N Pubodhya; Wasantha Rajapakshe (PLoS ONE)
This study explores the integration of sexual and reproductive health (SRH) education in Sri Lanka, utilizing the Health Belief Model (HBM) to predict the perceived quality of SRH education among non-state undergraduate students. In many Asian countries, including Sri Lanka, cultural resistance and skepticism often challenge SRH education initiatives. The research is based on a questionnaire survey, examining factors influencing the perceived quality of SRH education, such as cultural norms, embarrassment, attitudes, awareness, and institutional support. In recent years, the Sri Lankan telecom industry has experienced significant expansion and transformation, leading to a notable increase in mergers and acquisitions (M&A). This study investigates the impact of human resource practices on M&A performance, utilizing Lewin's Change Management Model as a framework. The research is based on a questionnaire survey, examining factors influencing the performance of M&A in Sri Lanka Telecom industry, such as communication (Unfreeze), training (Change), leadership (Refreeze), and performance (M&A outcomes). Structural Equation Modeling (SEM) reveals that communication significantly influences training (β = 0.800), while training has a strong effect on leadership (β = 1.062), both directly and indirectly via communication (β = 0.850). Additionally, performance is positively impacted by training (β = 0.819) and leadership (β = 0.459), with communication exerting a substantial indirect influence on performance (β = 0.655). These results underscore the necessity for an integrated approach that enhances organizational performance and adaptability in an evolving business landscape. To optimize M&A outcomes, organizations are encouraged to prioritize leadership development, invest in comprehensive training programs, and align communication strategies effectively. This research contributes valuable insights into the management of change within the telecom sector, promoting sustainable growth and success in future M&A endeavours.